To Check the Validity of Neoclassical Canon in Western MaharashtraAn Anthropometric Study - Laxmi Prashant Niva; Achelshwar R Gandotra; Rohini Rajesh Karambalekar (Journal of Clinical and Diagnostic Research, 2021)
Introduction: In ancient days, it was believed that attractive and harmonious faces were having certain fixed proportions known as neoclassical canons. These canons were used extensively by Leonardo Da Vinci, Durer in their art during renaissance. They served as guidelines for artists as well as for aesthetic surgeons for centuries and proved to be helpful till now. From ancient days to modern era, the exact formula of beauty is not yet calculated. The norms of beauty changes from country to country and race to race. A face is beautiful and shows harmonious features if the individual components are proportional, this is what is referred as facial balance. In ancient Greece, they calculated the formula for creation of art and these formulae are called as neoclassical canons. The classical Greek canons of facial balance are still foundation of modern reconstructive and aesthetic surgery. Aim: To check the validity of neoclassical canon in Western Maharashtrian population. Materials and Methods: This was an observational type of study carried out from March 2018 to January 2020. The validity of Naso-oral canon was checked in Western Maharashtrian population. According to this canon ideal mouth width (chch) (mouth width (distance between right and left corners of mouth called chelion)) is 1.5 times of Nose width/alar width (al-al) (alar width (distance between right and left ala of nose)). Mouth width=1.5 times of Nose width. However, the mouth width can be less than 1.5 times of nose width or mouth width can be greater than 1.5 times of nose width. This study was carried out in the five cities Sangli, Kolhapur, Islampur, Karad and Satara of Western Maharashtra, India. Total 1500 male and female students, 300 from each city, between the age group of 18-20 years were selected. Measurements were taken with the help of digital Vernier caliper. The methodology adopted for the measurements was taken from the guidelines given by Farkas LG in his book- “Anthropometric facial proportions in Medicine”. Results: In present study, total 68.33% subjects including males and females were having mouth width (ch-ch) lesser than one and half times of nose width/alar width (al-al) i.e., ch-ch <1.5 (al-al). Remaining 31.67% subjects were having mouth width greater than one and half times of nose width/alar width i.e., ch-ch >1.5 (al-al). Conclusion: Naso-oral neoclassical canon was not found valid in Western Maharashtrian young adults. In 78.32% male and 62.80% female population of Western Maharashtra, mouth width was found lesser than one and half times of nose width.